2021
DOI: 10.3168/jds.2020-19020
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Comparative estimation of colostrum quality by Brix refractometry in bovine, caprine, and ovine colostrum

Abstract: Newborn ungulates depend on the timely supply of colostrum containing sufficient immunoglobulins to obtain passive immunity against disease. Brix refractometry enables a rapid on-farm estimation of colostrum quality and has been intensively studied in bovines. However, the suitability of Brix refractometers for assessing colostrum quality in goats and ewes has been scarcely evaluated. The present study compared bovine, caprine, and ovine colostrum quality estimation using an optical Brix refractometer. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 33 publications
8
38
2
1
Order By: Relevance
“…The positive correlations between Brix and IgG are not surprising given the respective relationships between %Brix and total protein content in colostrum (r p = 0.81; p < 0.001; Figure 1d); this finding was similar to those detected in goats (r p = 0.89; p < 0.001) and sheep (r = 0.87; p < 0.001) [29]. Brix measurements are in fact related to total solids and thus indirectly to estimating IgG [40].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The positive correlations between Brix and IgG are not surprising given the respective relationships between %Brix and total protein content in colostrum (r p = 0.81; p < 0.001; Figure 1d); this finding was similar to those detected in goats (r p = 0.89; p < 0.001) and sheep (r = 0.87; p < 0.001) [29]. Brix measurements are in fact related to total solids and thus indirectly to estimating IgG [40].…”
Section: Discussionsupporting
confidence: 66%
“…Weaver et al (2000) [10] reported single radial immunodiffusion (sRID) [20][21][22] and enzyme-linked immunosorbent assay (ELISA) to be the only true and direct measures of colostrum or serum IgG [23][24][25]. IgG can also be measured indirectly by rapid on farm methods including refractometry, which represents an inexpensive, rapid, and accurate test that has shown a close relationship with IgG measured by laboratory methods for colostrum and serum samples in Bovines [1,2,[26][27][28][29], goat and sheep [29]. Brix refractometers have been promoted by the dairy industry as an effective on-farm rapid tool to estimate colostral IgG and colostrum quality [30].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study by Kessler et al [ 9 ], using an optical Brix refractometer, Brix values ranged from 11.4 to 34.6% and 15.4 to 40.0% in bovine and ovine colostrum, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In both species, Brix was highly correlated with IgG and protein concentrations (bovine, r = 0.98; ovine, r = 0.87) [ 9 ]. The Brix refractometer measures the total solutions dissolved and not specifically Ig, so differences in colostrum nutrient contribuite to a variation in the final estimate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation